Construction and operationalisation of sectorial brands: The case of the Brazilian winemaking sector from the perspective of different stakeholders - Dra Virginia Aparecida Castro; Janaina de Moura Engracia Giraldi; Jorge Henrique Caldeira de Oliveira (Wine Economics and Policy, 2018)
The objective of this article is to understand the process of construction and operation of sectorial brands (a type of shared brand) for the Brazilian winemaking sector, considering the perspective of different stakeholders: government agencies, associations, and managers of the wineries. The research was exploratory and qualitative, using techniques such as direct observation and in-depth interviews. The results showed that gains of dissemination and image are foreseen with the participation of the Brazilian winemaking sector in international fairs, in relation to the external market. In relation to the domestic market, it is concluded that it is necessary to continue investing in actions and projects, with the participation of the associations and commitment of the producers so that the Brazilian consumer knows and consumes the national product. The contributions of this article show that government agencies, associations, and wineries understand that the brand of the Brazilian winemaking sector is contributing to the development of the sector and that these actions must be continued. Thus, the joint work of all stakeholders involved should seek to improve the production process and improve the quality of the products to be marketed in the internal and external market.
Keywords: 330; Brazil winemaking sector; Sectorial brand; Shared brands